INTERPRETATION OF SMALL TO MODERATE SEISMICITY UNDER IRAZÚ VOLCANO - Cascante-Matamoros, Monserrat; Hernán Porras-Espinoza, Hernán Porras-Espinoza (Revista Geográfica de América Central., 2017)
Historically, Irazú volcano has experienced sporadic volcano-tectonic seismicity. Based on this seismic activity, we have calculated a total of 7 focal mechanisms using the polarity of first arrivals, and have calculated stress inversion using the PTB method. The results indicate that the seismic activity is between 0-6 km deep, mainly in the W flank of the volcanic massif. Focal mechanisms show a diverse cinematics, the angles of the planes have an average of 55°, and the direction of inclination is toward the SWW. Stress inversion suggests a pure extension with a value of R’= 0,5. Therefore, the depth of the seismic events and the average angle of the planes makes us suppose that the brittle-ductile transition is above the one theoretically established. We suggest that the seismic source under the Irazú Volcano is directly related to the presence of magma near the surface, which causes the thinning of the crust and the related normal faults.